2021
DOI: 10.1080/21678421.2021.1907412
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-phenotype correlations of KIF5A stalk domain variants

Abstract: The kinesin family member 5A (KIF5A) motor domain variants are typically associated with hereditary spastic paraplegia (HSP) or Charcot-Marie-Tooth 2 (CMT2), while KIF5A tail variants predispose to amyotrophic lateral sclerosis (ALS) and neonatal intractable myoclonus. Variants within the stalk domain of KIF5A are relatively rare. We describe a family of three patients with a complex HSP phenotype and a likely pathogenic KIF5A stalk variant. More family members were reported to have walking difficulties. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…These results support the idea that the new C-terminal tail in ΔExon27 is required to confer gain of toxicity through the relief of autoinhibition and through self-association/aggregation of the mutant motors. In line with this notion, several single nucleotide deletion variants of KIF5A have also been identified in ALS patients (de Boer et al , 2021) which result in a C-terminal tail similar to that of the exon 27-skiping variants: Variants c2987delA (p.Asp996fs), c.2989delA (p.Asn997fs), and c.2996delA (p.Asn999fs) cause one nucleotide frame shifting at amino acid positions Asp996, Asn997, and Asn999 at the protein level, respectively ( Fig. S5 ).…”
Section: Discussionmentioning
confidence: 69%
“…These results support the idea that the new C-terminal tail in ΔExon27 is required to confer gain of toxicity through the relief of autoinhibition and through self-association/aggregation of the mutant motors. In line with this notion, several single nucleotide deletion variants of KIF5A have also been identified in ALS patients (de Boer et al , 2021) which result in a C-terminal tail similar to that of the exon 27-skiping variants: Variants c2987delA (p.Asp996fs), c.2989delA (p.Asn997fs), and c.2996delA (p.Asn999fs) cause one nucleotide frame shifting at amino acid positions Asp996, Asn997, and Asn999 at the protein level, respectively ( Fig. S5 ).…”
Section: Discussionmentioning
confidence: 69%
“…Some studies had reported SOD1 mutations in patients with atypical phenotypes suggestive of pSMA, dSMA, CMT or spastic paraplegia [20,[23][24][25][26], but this study confirms a causal role. Thus, SOD1 should join the list of genes that can present with a wide spectrum of motor phenotypes (such as KIF5A, CHCHD10, VAPB, FIG4) [7,27,28], where its analysis should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of this pleiotropy are not entirely known. In some genes, a mutational hotspot predisposes to one or another phenotype [27]. In other genes it seems more dependent on other genetic or epigenetic factors because the same mutation can present with different phenotypes in diverse populations [7,28].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the anterograde axonal transport motor KIF5A stands out as a risk factor for the survival of long axons in multiple disorders, including hereditary spastic paraplegia (HSP) [ 95 ], Charcot-Marie-Tooth (CMT) disease Type 2 [ 96 ], adult onset distal SMA [ 97 ], and possibly neonatal intractable myoclonus [ 98 ], although whether this last one involves axon loss is less clear. Intriguingly, there may be a degree of domain specificity regarding which KIF5A variant contributes to which disorder, with motor domain variants predominantly linked to HSP and CMT2 and tail (cargo-binding) domain variants to ALS and neonatal intractable myoclonus, although there are exceptions [ 99 ]. Nevertheless, the phenotype of the null mice, and their neurons in primary culture [ 100 ] clearly indicate that KIF5A is essential for both axonal transport and the ability to sustain long axons.…”
Section: Mechanisms Of Axon Loss In Alsmentioning
confidence: 99%